Proceedings of the 4th International Conference on Business, Management and Finance 2021
DOI: 10.33422/4th.icbmf.2021.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Usage of Online Shopping in Albania

Abstract: The increase in the use of the internet worldwide has shifted consumers' attention to online shopping. The increased confidence in technology, ability to use information and communication technology and online payment methods are changing consumer buying behaviour away from traditional methods. Online shopping is showing encouraging progress among customers in Albania. An incentive for the increase in online shopping is the impact of the pandemic situation of COVID-19 that forced foreign and domestic retailers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
0
0
Order By: Relevance
“…Regarding website design, Tian Zhenshi believes that perceived ease of use has a positive effect on consumer website usage intention [19], and this result is consistent with other scholars [20]. An empirical analysis was conducted on the relationship between sex and online shopping intention, and it was also found that perceived ease of use had a significant positive impact on online shopping intention [21][22].…”
Section: Important Resultssupporting
confidence: 72%
“…Regarding website design, Tian Zhenshi believes that perceived ease of use has a positive effect on consumer website usage intention [19], and this result is consistent with other scholars [20]. An empirical analysis was conducted on the relationship between sex and online shopping intention, and it was also found that perceived ease of use had a significant positive impact on online shopping intention [21][22].…”
Section: Important Resultssupporting
confidence: 72%
“…However, before the pandemic, the age group of 25-34 showed higher engagement in e-shopping compared to other age groups. This finding that younger people were more involved in e-shopping is supported by the existing literature [9,28,31,39]. However, contrary evidence also exists, indicating that age negatively influences e-shopping behavior [9,28,31,39].…”
Section: Determinants Of Household Essentials Shoppingsupporting
confidence: 77%
“…This finding that younger people were more involved in e-shopping is supported by the existing literature [9,28,31,39]. However, contrary evidence also exists, indicating that age negatively influences e-shopping behavior [9,28,31,39].…”
Section: Determinants Of Household Essentials Shoppingsupporting
confidence: 77%
See 2 more Smart Citations